Non-linear free boundary simulations of the plasma response to resonant magnetic perturbations in ASDEX Upgrade plasmas - Mitterauer, V; Hoelzl, M; Willensdorfer, M; Dunne, M; Schwarz, N; Artola, J; Team, JOREK; Team, ASDEX Upgrade (Journal of physics. Conference series, 2022)
A promising method for the control of Edge Localized Modes (ELMs) in H-Mode tokamak plasmas is the application of Resonant Magnetic Perturbations (RMPs), where small helical field perturbations are introduced into the plasma via a set of external coils. While RMPs are used for suppression of ELMs in many present-day tokamaks, the mechanisms that lead to RMP-ELM control are still subject of debate. Here, we use the non-linear MHD code JOREK to investigate the penetration of the magnetic perturbation fields into ASDEX Upgrade (AUG) plasmas. We present an extension of the coupled JOREK-STARWALL code, that replaces the commonly used fixed boundary treatment with a free boundary treatment. Instead of prescribing the magnetic field at the boundary according to the vacuum field using Dirichlet boundary conditions, natural boundary conditions are applied, so that the magnetic field and plasma current density are evolving freely at the boundary. This allows a fully self-consistent development of the plasma response and the magnetic perturbation in the whole computational domain. The direct comparison of both approaches demonstrates that the artificial suppression of the plasma response with the fixed boundary treatment reduces the excitation of marginally stable modes. An overall larger perturbation is observed using the free boundary approach. The presented simulations are performed in realistic geometry with fully realistic plasma parameters and plasma flows based on reconstructions of experimental AUG equilibria. While the use of realistic plasma parameters makes the simulations particularly challenging, it also allows for quantitative comparisons to the experiment. When the RMP induced corrugation of the boundary is compared to electron density measurements from the lithium beam emission spectroscopy, only the free boundary approach shows excellent agreement with the experiment.